Penganutan Agama Islam dan Kristian dalam Kalangan Masyarakat Kadazan Dusun di Sabah - Sintang, Suraya (Jurnal Usuluddin, 2003)
he uniqueness of Sabah's society is not only potrayed by its various ethnics, dialects and cultures, but also the religious adherence of its natives which comprised of two sub-categories known as 'Muslim Bumiputera' and 'Non-Muslim Bumiputera'. This phenomenon shows that the social structure of Sabah is based on religions. Hence the native of Kadazandusun is selected as a focal study to identify the phenomenon of religious adherence in Sabah. This paper initiates to discuss the tendency of Kadazandusun native for choosing Islam and Christianity as their religions. In comparison between these two religions, the Kadazandusun community tend to choose Christianity. The research findings show the numbers of Christians are larger than Muslims with the ratio 4:1. There are various factors which contribute to the tendency of choosing Islam and Christianity among Kadazandusun society. Those factors are related to the historical dissemination of Islam and Christianity, the changes of Sabah's political climate, the method of religious spread and the inter-marriage culture among Sabahan people.